2023
DOI: 10.3390/v15112186
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Genotype H: Epidemiological, Molecular, and Clinical Characteristics in Mexico

Arturo Panduro,
Sonia Roman,
Saul Laguna-Meraz
et al.

Abstract: The hepatitis B virus (HBV), comprising of ten genotypes (A-J), has been a silent threat against humanity, constituting a public health problem worldwide. In 2016, the World Health Organization set forth an impressive initiative for the global elimination of viral hepatitis by 2030. As the target date approaches, many nations, particularly in the Latin American region, face challenges in designing and implementing their respective elimination plan. This review aimed to portray the state of knowledge about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Hence, derived from S8 , four new Intra-SG structures ( S8Ha ′, S8Hb ′, S8Hc ′ and S8Hd ′, Table S1†) were designed for recognizing four short single-stranded DNA segments from the HBV gene ( Ha , Hb , Hc and Hd ). 40,41 The HBV has been regarded as a major threat to human health and its infection could lead to liver diseases ( e.g. , hepatocellular carcinoma).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, derived from S8 , four new Intra-SG structures ( S8Ha ′, S8Hb ′, S8Hc ′ and S8Hd ′, Table S1†) were designed for recognizing four short single-stranded DNA segments from the HBV gene ( Ha , Hb , Hc and Hd ). 40,41 The HBV has been regarded as a major threat to human health and its infection could lead to liver diseases ( e.g. , hepatocellular carcinoma).…”
Section: Resultsmentioning
confidence: 99%
“…To date, five HBV genotypes may be significant for PerMed-Nut in Mexicans with different clinical implications. Among these, HBV genotypes H is predominant followed by G, F, A, and D which circulate in patients according to genetic and sociodemographic backgrounds ( 82 , 83 ). Based on molecular epidemiology data, HBV genotypes A and D discovered in Mexico are deemed exotic when compared to the Americas’ prevalent H and F. Indeed, phylogenetic examination of those genotypes suggested that A2 originated in Europe and D4 in Africa.…”
Section: Managing Chronic Liver Disease Using a Permed-nut Approachmentioning
confidence: 99%
“…Regarding the clinical result, HBV genotypes A and D have been identified in individuals with chronic infection, but genotype H is common in occult hepatitis B cases and exhibits a high degree of adaptation among the local people ( 82 ). Interestingly, sub-genotype F1b native to South America and linked to HCC in Native Alaskans ( 84 ) and Native Peruvians ( 85 ) has been found in Mexican patients ( 86 ).…”
Section: Managing Chronic Liver Disease Using a Permed-nut Approachmentioning
confidence: 99%
See 1 more Smart Citation